Effects of non-pharmacological approaches on anxiety, agitation and physiologic parameters in weaning from mechanical ventilation: A systematic review: Non-pharmacological approaches on weaning from MV - Şengör, Kübra; Çavdar, İkbal and Polat, Eda (Journal of Surgery and Medicine, 2025)
Background/Aim: Mechanical ventilator weaning refers to the incremental reduction of ventilatory support, facilitating a return to spontaneous breathing. It is essential that this process be carried out by skilled healthcare professionals equipped with both expertise and sound judgment to ensure it is performed at the optimal time and with the most appropriate methodologies. Such diligence is crucial in mitigating the morbidity and mortality associated with the protraction of mechanical ventilation (MV). The extant literature has explored the efficacy of various integrative, non-pharmacological interventions—including music therapy, guided imagery, reflexology, and aromatherapy—in managing the symptomatic burden experienced during both MV and its weaning phase. This study aims to systematically review the findings of investigations that assess the impact of these complementary therapeutic modalities employed by nurses on anxiety, agitation, and the physiological parameters of patients undergoing weaning from mechanical ventilation. Methods: PubMed, CINAHL, Cochrane Library, Scopus, and Google Scholar databases were systematically searched using the key terms ‘Mechanical ventilator weaning and complementary therapy or non-pharmacological approaches’ and ‘Mechanical ventilator weaning and/or music therapy, reflexology.’ The search strategy was formulated based on the Patient-Intervention-Comparison-Outcome (PICO) framework: P—Adult intensive care patient cohort; I—Application of non-pharmacological approaches in the context of weaning from mechanical ventilation; C—Standard routine care; O—Outcomes related to anxiety, agitation, and physiological parameters. The 10 most pertinent studies, meeting predefined inclusion and exclusion criteria, were selected, encompassing a total of 750 participants. The predominant study design was the randomized controlled trial (RCT). The interventions examined across these studies primarily involved music and reflexology therapies. Results: Most of the studies reviewed that the use of non-pharmacological interventions reduces patients’ symptoms such as anxiety, agitation, and pain in patients. These methods also contribute to the stabilization of physiological parameters within normal ranges. Moreover, reflexology has been shown to expedite the weaning process from mechanical ventilation, thereby reducing the risk of prolonged mechanical ventilation, a significant challenge for patients and healthcare professionals. Conclusion: Complementary therapy used in the process of mechanical ventilator weaning is an appropriate intervention to be used to manage patients’ symptoms such as anxiety, agitation, and pain.